MORPHOLOGICAL AND MOLECULAR GENETIC DESCRIPTION OF THE MALARIOUS MOSQUITO ANOPHELES SUPERPICTUS GRASSI (1899) IN THE SURKHANDARYA NATURAL GEOGRAPHICAL REGION (Scientific journal of the Fergana State University, 2023)
This article published a study conducted on malarial mosquitoes of the genus Anopheles Meigen (1818) in the Surkhandarya region. In particular, information is given on the basis of the coordinates of observation points on morphological features and the results of molecular genetic analysis of the species Anopheles superpictus Grassi (1899) from the genus Anopheles Meigen (1818), belonging to the family Culicidae.